Post a New Question


posted by .


(1/cos)^2 times (1/tan)-(1/tan)=tan

(1/cos^2) times (-2/tan)=tan

(-2/cos^2tan)times tan=tan(tan)

sq. root of (-2/cos^2)= sq. root of (tan^2)

sq. root of (2i)/cos=tan

I'm not sure if I did this right. If I didn't, can you show me the correct steps?

Thanks, I appreciate it.

  • Trig. -

    sec^2(x)cot(x) - cot(x) = tan(x)

    Convert everything to sine and cosine using the identity tan(x) = sin(x)/cos(x).

    cos^-2(x)(cos(x)/sin(x)) - cos(x)/sin(x) = sin(x)/cos(x)

    1/( cos(x)sin(x) ) - cos(x)/sin(x) = sin(x)/cos(x)

    Note: it is important to write sin(x) as opposed to sin, because you may find equations that include different parameters -- sin(x) and sin(2x), for example.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question